2016
DOI: 10.1038/ki.2015.320
|View full text |Cite
|
Sign up to set email alerts
|

AT1 receptor antagonism before ischemia prevents the transition of acute kidney injury to chronic kidney disease

Abstract: Despite clinical recovery of patients from an episode of acute kidney injury (AKI), progression to chronic kidney disease (CKD) is possible on long-term follow-up. However, mechanisms of this are poorly understood. Here, we determine whether activation of angiotensin-II type 1 receptors during AKI triggers maladaptive mechanisms that lead to CKD. Nine months after AKI, male Wistar rats develop CKD characterized by renal dysfunction, proteinuria, renal hypertrophy, glomerulosclerosis, tubular atrophy, and tubul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
71
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 48 publications
5
71
1
Order By: Relevance
“…Since none of the ATN patients in this study were being treated with RAS inhibitors at the time of biopsy, the effect of RAS blockade on urinary AGT and ATN severity was unknown. However, animal studies have already shown a correlation between RAS blockade and improved AKI outcomes [22,23]. Further studies to investigate the role of RAS inhibition in various AKI populations would be helpful to extend our observations, and to confirm the role of intrarenal RAS in the pathogenesis of AKI.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Since none of the ATN patients in this study were being treated with RAS inhibitors at the time of biopsy, the effect of RAS blockade on urinary AGT and ATN severity was unknown. However, animal studies have already shown a correlation between RAS blockade and improved AKI outcomes [22,23]. Further studies to investigate the role of RAS inhibition in various AKI populations would be helpful to extend our observations, and to confirm the role of intrarenal RAS in the pathogenesis of AKI.…”
Section: Discussionsupporting
confidence: 53%
“…Urinary AGT could potentially be added to these biomarkers to form a biomarker panel, and would probably be particularly A linkage between intrarenal RAS and kidney injury has been increasingly recognized. Animal studies have noted an association between inhibition of the RAS and improved outcomes of AKI [22,23]. Clinical studies have described urinary AGT as a novel predictive and prognostic biomarker of AKI [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Many clinical trials have proved the specific renoprotective effect of RAS inhibition by ACE inhibitor/ARB for patients with diabetic or proteinuric non-diabetic CKD to reduce disease progression and mortality515253. However, RAS inhibition is usually avoided during the acute phase of AKI patients, and the role of RAS activity in acute phase and injury severity is not clear indeed212254. Based on findings that intrarenal RAS was activated in repairing kidneys in spite of complete recovery of plasma parameters for renal function assessment one month after acute injury, our previous study has shown that RAS inhibition with losartan in mouse AKI survivors can prevent the development of ensuing CKD and mortality20.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, animal studies have demonstrated that activation of intrarenal renin–angiotensin system (RAS) after AKI underlies the possible mechanism for development and progression of ensuing CKD202122. To get insight into the clinical application of RAS inhibitor and its impact on development of ensuing CKD in AKI survivors with complete renal recovery, we studied the outcomes and relevant risk factors of cardiac surgery–associated AKI (CSA-AKI) patients who did not have CKD history before surgery in our prospectively collected observational cohort.…”
mentioning
confidence: 99%
“…40 Losartan-treated mice were shown to have less renal injury by suppressing transdifferentiation and the resultant ECM synthesis. 41 Notably, Ang II can induce transdifferentiation and ECM deposition, albeit less efficaciously than TGF-b1. 6 Angiotensin II incubation for 24 hours significantly increased the expression of TGF-b1.…”
Section: Discussionmentioning
confidence: 99%